2015
DOI: 10.1002/adom.201500301
|View full text |Cite
|
Sign up to set email alerts
|

Coupling and Interlayer Exciton in Twist‐Stacked WS2 Bilayers

Abstract: and Hofstadter's butterfl y. [ 10,11 ] In vertical stacked MoS 2 /WS 2 heterostructure which was fabricated by transferring MoS 2 fl akes to WS 2 fl akes, a new photoluminescence (PL) peak emerged after annealing in vacuum which is dictated by charge transfer and band normalization between the WS 2 and MoS 2 layers. [ 12 ] Also, indirect band gap peak of 15° twisted MoS 2 grown by chemical vapor deposition (CVD) method has a smaller redshift due to the larger interlayer distance compared to the ones of AA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 30 publications
9
75
1
Order By: Relevance
“…All the results presented here are of S1 sample and those of S2 sample are presented in Supplementary material. The Raman spectrum of monolayer WS 2 is shown in Figure 1b, and the Raman interval between out-of-plane A 1g mode and inplane E 1 2g mode is around 61.7 cm −1 , which is in accordance with previous reports [47,48]. The schematic of DC PL and GS is the ground state.…”
Section: Introductionsupporting
confidence: 88%
“…All the results presented here are of S1 sample and those of S2 sample are presented in Supplementary material. The Raman spectrum of monolayer WS 2 is shown in Figure 1b, and the Raman interval between out-of-plane A 1g mode and inplane E 1 2g mode is around 61.7 cm −1 , which is in accordance with previous reports [47,48]. The schematic of DC PL and GS is the ground state.…”
Section: Introductionsupporting
confidence: 88%
“…1i presents the Raman spectra of WS 2 NRs with two primary peaks corresponding to the in-plane E 1 2g and out-of-plane A 1g modes, respectively. Moreover, we found that the A 1g /E 1 2g ratio for multilayer WS 2 NR (~1.23) is higher than the A 1g /E 1 2g ratio of monolayer WS 2 NR (~1.1) and monolayer WS 2 NP (~0.34), which may result from the interlayer coupling effect in the neighboring layers [28,29]. This distinct Raman feature can be viewed as a probe to differentiate monolayer and multilayer WS 2 NRs.…”
Section: Controllable Growth and Characterization Of Ws 2 Nrsmentioning
confidence: 79%
“…For example, twisted bilayer WS 2 flakes with various twist angles exhibited strong PL and quasi-direct bandgaps compared with their conventional AA or AB stacking bilayers, implying an enlarged interlayer distance and a weaker interlayer coupling. 123 The unprecedented magic angle of twisted bilayer graphene and the resulting superconductivity surprised researchers while h-BN is crucial to fabricate twisted bilayer graphene as a pick-up tool and a capping layer. Two graphene monolayers, stacked by a small twist angle, form a moiré pattern with a period related to the twist angle.…”
Section: Magic Angle In Twisted Bilayer Graphene Encapsulated By H-bnmentioning
confidence: 99%
“…By tuning the rotational angle, interlayer coupling in Gr/Gr can be precisely controlled and employed to modulate their electronic and optical properties. For example, twisted bilayer WS 2 flakes with various twist angles exhibited strong PL and quasi‐direct bandgaps compared with their conventional AA or AB stacking bilayers, implying an enlarged interlayer distance and a weaker interlayer coupling 123 …”
Section: The Functionality Of Thick H‐bnmentioning
confidence: 99%